Revista Educação Especial: a bibliometric study of scientific production in the field of Special Education - Rosemary Cristina da Silva; Maria Cristina P. I. Hayashi (Universidade Federal de Santa Maria (UFSM), 2013)
This article presents the results a bibliometric study of the scientific production in the field of Special Education, that aimed to analyze the 147 articles published from 2000-2006 including those published online, totaling 14 issues in the Revista Educação Especial. This journal was chosen as the unit of analysis because it is being the most long-standing journal in the country. The bibliometric analysis of the articles and citations allowed build the following indicators of scientific production: a) for articles published: evolution of articles published; typology of the articles, number of pages of articles, authors of the articles, scientific collaboration in the authorship; productivity authors; transiente of the authors; gender, geographic origin and institutional affiliation of the authors; b) about the citations made by the authors: thematic of the articles, authors of the citations; the source updating level; origin, typology, languages and format of the sources cited; identification of the resources periodic cited; the core of the journal and secondary areas the field of Special Education. The bibliometric analysis this scientific production this journal demonstrated its consolidation in the area of Special Education. The study Bibliometric of citations made by the authors allowed verify the interdisciplinarity of Special Education with other areas of knowledge. It was verified as to represent the field of Special Education as a medium for information, as well as facilitate the dissemination of research carried out in this area.